2002
DOI: 10.1182/blood.v99.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated polysaccharides increase plasma levels of SDF-1 in monkeys and mice: involvement in mobilization of stem/progenitor cells

Abstract: It was previously reported that treatment with the sulfated polysaccharide fucoidan or the structurally similar dextran sulfate increased circulating mature white blood cells and hematopoietic progenitor/stem cells (HPCs) in mice and nonhuman primates; however, the mechanism mediating these effects was unclear. It is reported here that plasma concentrations of the highly potent chemoattractant stromal-derived factor 1 (SDF-1) increase rapidly and dramatically after treatment with fucoidan in monkeys and in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
184
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(196 citation statements)
references
References 47 publications
9
184
0
3
Order By: Relevance
“…30,31 SDF-1 is known to mediate the mobilization and migration of bone marrow-derived progenitor cells in vivo. 32 SP has also been shown to have a stimulatory effect on human bone marrow stem cells in vitro by interacting with bone marrow supporting stromal cells. 33 Therefore, it is possible to speculate that an increase in VEGF and SP levels may stimulate bone marrow, and enhance progenitor cell mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 SDF-1 is known to mediate the mobilization and migration of bone marrow-derived progenitor cells in vivo. 32 SP has also been shown to have a stimulatory effect on human bone marrow stem cells in vitro by interacting with bone marrow supporting stromal cells. 33 Therefore, it is possible to speculate that an increase in VEGF and SP levels may stimulate bone marrow, and enhance progenitor cell mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…37 To establish a role of SDF-1 in hepatic regeneration from oval cells, rats were injected with fucoidan. This sulfated polysaccharide binds to SDF-1, releases the chemokine from cell membrane-associated heparan sulfate proteoglycans, 27 and could therefore inhibit its biological activity. Indeed, in our AAF/PH model, fucoidan markedly decreased oval cell accumulation in a majority of treated rats, suggesting that SDF-1 promotes the activation of Hering duct-located quiescent stem cells into oval cells and/or stimulates oval cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…27 These experiments were performed in Wistar rats because preliminary trials showed that this strain tolerated this compound better than Fischer rats. Livers were examined after 4 days of a treatment which was well tolerated, as judged by the absence of difference in the weight of treated and control animals at the end of the experiment.…”
Section: Effect Of Fucoidan On Oval Cell Proliferationmentioning
confidence: 99%
“…Both sustained elevations of SDF-1 in NOD/SCID mice delivered by an adenoviral vector delivery system [34][35][36] , and chronic administration to the animals of SDF-1 peptide analogs 37,38 , result in mobilization of stem/ progenitor cells. In addition, increased plasma SDF-1 levels are also observed during mobilization induced by sulfated glycans 39 . Although G-CSF-induced stem/progenitor cell mobilization is not associated with increased levels of SDF-1 in the blood, this treatment reduces the levels of SDF-1 in the marrow and alters CXCR4 expression by stem/progenitor cells 40,41 by inducing a proteolytic environment 42 .…”
Section: Introductionmentioning
confidence: 97%